The Relation between a Three-Sector Economic Model with Social Inequality in Poland, Differentiated by Region - Anna LUDWICZAK (Communications of International Proceedings, 2020)
One of the most vital goals of any national policy is economic development. This however poses the interesting question of whether this should be treated as a means to an end or as an end in itself.  Everyone surely expects that economic development inexorably delivers both an improved quality of life and social wellbeing. For this reason we have differentiated between the concept of economic growth and development/efficiency with socio-economic-related wellbeing; thus clearly demonstrating the multi-dimensional nature between these two areas.  This study aims to investigate the relationship between the economical structure in a three-sector system with social inequalities according to the diversity of regions found in Poland. Straightforward statistics were used to seek for correlations between the factors under study. A strong correlation was found between employment structure in those regions with existing social inequalities; especially in poverty and social exclusion.
Keywords: Sustainable Development; Economic Structure; Quality of Life; Regional Diversity.